The set of discontinuity points of separately continuous functions on the products of compact spaces - Mykhaylyuk, V. V. (Methods of Functional Analysis and Topology, 2007)
We solve the problem of constructing separately continuous functions on the product of compact spaces with a given set of discontinuity points. We obtain the following results. 1. For arbitrary Čech complete spaces X, Y, and a separable compact perfect projectively nowhere dense zero set EX× Y there exists a separately continuous function f:X× Y→R the set of discontinuity points, which coincides with E. 2. For arbitrary Čech complete spaces X, Y, and nowhere dense zero sets AX and BY there exists a separately continuous function f:X× Y→R such that the projections of the set of discontinuity points of f coincides with A and B, respectively. We construct an example of Eberlein compacts X, Y, and nowhere dense zero sets AX and BY such that the set of discontinuity points of every separately continuous function f:X× Y→R does not coincide with A× B, and a CH-example of separable Valdivia compacts X, Y and separable nowhere dense zero sets AX and BY such that the set of discontinuity points of every separately continuous function f:X× Y→R does not coincide with A× B.